Functional Outcome by Evaluation of DASH Score on Drop Hand Patient Treated with Jones’ Tendon Transfer: A Retrospective Study - Sumarwoto, Tito; Hadinoto, Seti Aji; Pradhana, Adhitya Indra ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2021)
Background: Drop hand, resulting from radial nerve injuries, causes functional and structural disabilities. Tendon transfer becomes the last option when nerve repair fails to achieve restoration. The most popular method is the Jones tendon transfer to restore wrist dorsiflexion and extension of the thumb and fingers. The Disabilities of the Arm, Shoulder, and Hand (DASH) score measures functional outcomes in patients with upper extremity injuries. This study aimed to assess the functional outcome and evaluate the DASH score in drop hand patients who underwent Jones tendon transfer surgery at Prof. Dr. R. Soeharso Orthopaedic Hospital Surakarta. Methods: Data collected from medical records between January 2014 and June 2016 were evaluated based on functional outcome and DASH score. Eleven patients were included, comprising ten male patients (90.9%) and one female patient (9.1%). The mean age of the patients was 27.4 years. The right arm was the most frequently injured, accounting for eight patients (72.7%), while the left arm was injured in three patients (27.3%). Results: The DASH score evaluation indicated minimal disability in ten patients (90.9%) and moderate disability in one patient (9.1%). The average score was 12.48, indicating that most patients could cope with most daily living activities postoperatively.Conclusions: Surgical intervention for drop hand due to radial nerve palsy using the Jones tendon transfer technique yielded a satisfactory functional outcome based on the DASH score.